Sistem pakar deteksi penyakit jagung dengan metode forward chaining di kelompok tani lestari desa bandar kumbul - Muliadong pane, Siti rahma pane; Subagio, S; Ritonga, Wahyu Azhar (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
One of the causes of the failure of hybrid corn cultivation activities is pests and diseases which are the result of complex or unbalanced interactions between the three components in weak aquatic ecosystems, ferocious pathogens and deteriorating environmental quality. With that, it is necessary to have an application that can help farmers to take care of corn plants so that they are not attacked by pests and diseases. The application system created in this study is an expert system that can analyze the types of diseases in corn. The expert system in this study uses the Forward Changing method. This expert system is expected to be able to assist farmers in solving farmer problems in detecting corn disease by making applications using WEB, with MySQL and Xampp databases.